2012
DOI: 10.1016/j.addbeh.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between indicators of acculturation and tobacco dependence among Spanish-speaking Latino smokers

Abstract: The current study utilized regression analyses to explore the relationships among demographic and linguistic indicators of acculturation, gender, and tobacco dependence among Spanish-speaking Latino smokers in treatment. Additionally, bootstrapping analyses were used to examine the role of dependence as a mediator of the relationship between indicators of acculturation and cessation. Indicators of time spent in the United States were related to indicators of physical dependence. Preferred media was related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[2][3][4][5][6] Acculturation to an American lifestyle is the leading explanation for these phenomena. 2,6,8,[10][11][12][13][14][15] Using national data, Khodr et al reported an increased rate of gastroschisis among infants of more acculturated, non-teen Hispanic mothers. 19 In contrast, Ramadhani et The incidence of gastroschisis is rising and significantly exceeds that of omphalocele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Acculturation to an American lifestyle is the leading explanation for these phenomena. 2,6,8,[10][11][12][13][14][15] Using national data, Khodr et al reported an increased rate of gastroschisis among infants of more acculturated, non-teen Hispanic mothers. 19 In contrast, Ramadhani et The incidence of gastroschisis is rising and significantly exceeds that of omphalocele.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] However, this advantage is limited to Mexico-born mothers, [7][8][9] suggesting that lifelong minority status and/or acculturation to an American lifestyle are risk factors for adverse birth outcome. 2,6,8,[10][11][12][13][14][15] Using national vital record data, a recent study found that the infant mortality rate of term births to US-born Mexican American mothers exceeded that of their Mexico-born counterparts. 16 Although congenital anomalies were the leading cause of first year mortality in both subgroups of term infants, maternal birth in the United States (compared with Mexico) was not associated with increased infant mortality rates due to congenital anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it represents yet another prognostic indicator that may not be useful to apply to Latino smokers. As such, there have been repeated calls for research into the non-physical aspects of tobacco dependence as determinants of smoking and cessation among Latinos (Castro et al, 2012;Reitzel et al, 2009;Zhu, Pulvers, Zhuang, & Baezconde-Garbanati, 2007).…”
Section: Physical Dependencementioning
confidence: 99%
“…Comprehensive self-report measures of tobacco dependence that tap into multiple social and cognitive (as well as physical) aspects of tobacco dependence have emerged in recent years (e.g., Etter, Le Houezec, & Perneger, 2003;Piper et al, 2004;Shiffman, Waters, & Hickcox, 2004;Smith et al, 2010), and research using such measures with Latino smokers is beginning to emerge (e.g., Castro et al, 2012;Kendzor, Businelle, Reitzel, Rios, et al, 2014). However, this is occurring in the absence of known published studies that explicitly examine whether or not the psychometric structure and predictive utility of these scales are similar for Latinos compared to other racial/ethnic groups of smokers.…”
Section: Physical Dependencementioning
confidence: 99%
“…Another study found that clients enrolled in CTN clinical trials were more likely to have full-time employment and higher educational attainment (34). Further, we did not assess acculturation or immigration/nativity, which may be associated with smoking prevalence and CPD (35), quit attempts (36), and nicotine dependence (37) in Latinos, since these variables were not part of the original study goals and thus were not included on the survey. However, all surveys were completed in English, and responding in English to English-language data collection instruments has been linked to high acculturation (38).…”
Section: Discussionmentioning
confidence: 99%